Sufficient condition for existence of solutions for higher-order resonance boundary value problem with one-dimensional p-Laplacian - Liu Yang; Chunfang Shen; Xiping Liu (Electronic Journal of Qualitative Theory of Differential Equations, 2007)
By using coincidence degree theory of Mawhin, existence results for some higher order resonance multipoint boundary value problems with one dimensional p-Laplacian operator are obtained.